Diastereoselective Ireland-Claisen rearrangements of substituted allyl β-amino esters: applications in the asymmetric synthesis of C(5)-substituted transpentacins. - Davies, S; Fletcher, A; Lee, J; Roberts, P; Souleymanou, M; Thomson, J; Zammit, C (2014)
The diastereoselective Ireland-Claisen rearrangement of a range of substituted allyl β-amino esters gave the corresponding enantiopure α-substituted-β-amino esters with good diastereoselectivity. The application of this methodology in the asymmetric synthesis of a range of C(5)-substituted 1,2-anti-1,5-syn-transpentacins was demonstrated by the rearrangement of a range of β-amino esters derived from sorbic acid, followed by esterification, ring-closing metathesis, hydrogenolytic deprotection/reduction, and hydrolysis, which gave the C(5)-substituted transpentacins in only 9 steps from commercially available starting materials.